Sikap Ikhwanul Muslimin tentang Nasionalisme dan Relevansinya dengan Konsepsi Ummah - Zen, M. Anwar (Prodi Siyasah Jinayah (Hukum Tata Negara dan Hukum Pidana Islam) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2013)
Abstract: This article discusses about the attitude of the Muslim Brotherhood on nationalism and its relevance to the concept of ummah. Nationalism, for the Muslim Brotherhood, is a love of the homeland, liberating the land from occupation, and strengthening brotherhood. Nationalismâs goal is to guide Muslim men toward the light of Islam and to raise the banner of Islam highly in each hemisphere in reaching the worldly prosperity and merely for the sake of gaining the pleasure of Allah. The Muslim Brotherhoodâs nationalism indicates a universalism which is implication of the belief bond. Therefore, their concept of nationalism is universal since it is not restricted by races, territories, and geographies. Furthermore, the attitude of the Muslim Brotherhood also indicate the orientation of the divinity that Islam can colors in every human life for the sake of gaining the pleasure of Allah and prosperity in the worldly life.Keywords: Muslim brotherhood, nationalism, ummah